Real and Convex Analysis - Çınlar, Erhan; Vanderbei, Robert J. (Undergraduate Texts in Mathematics,, 2013)
This book offers a first course in analysis for scientists and engineers. It can be used at the advanced undergraduate level or as part of the curriculum in a graduate program.    The book  is  built around metric spaces. In the first three chapters, the authors lay the foundational material and cover the all-important "four-C's": convergence, completeness, compactness, and continuity. In subsequent chapters, the basic tools of analysis are used to give brief introductions to differential and integral equations, convex analysis, and measure theory.    The treatment is modern and aesthetically pleasing. The book contains  detailed illustrations, examples and exercises. It lays the groundwork for the needs of classical fields as well as the important new fields of optimization and probability theory.